Biofeedback eletromiográfico e parâmetros da dinamometria isocinética de joelho e tornozelo de jogadores de futebol amador - Baron, Carina Elias; Secchi, Leonardo Luiz Barretti; Greve, Júlia Maria D´Andréa; Lima, Vasthi Oliveira de; Carvalho, Viviane Ribeiro (Acta Fisiátrica, 2010)
Electromyography has been used to evaluate the voluntary control of muscular activity. One of the highlights among the techniques is electromyography biofeedback (EMGBio), which works as a facilitator of neuromotor development, including playing sports. Objective: To analyze the effect of EMGBio within the isokinetic parameters of knee flexion and extension and ankle inversion and eversion in amateur soccer players. Subjects: Two randomized groups of fourteen male amateur soccer players: Training group (TG) – seven athletes, with an age of 23 ± 2 (22 and 28) years old, body mass 75.7kg ± 4.0kg (72 and 80), height 182cm ± 4cm (176 and 188) and Control Group (CG) – seven athletes, with an age of 24 ± 2 (21 and 28) years old, body mass 72.3kg ± 9.4kg (59 and 79), height 175cm ± 5cm (169 and 180). Methods: all athletes were evaluated by a clinical protocol: anamnesis, occurrence of injuries and visual analogue scale of pain and were subjected to knee flexion and extension and ankle inversion and eversion isokinetic dynamometry. The training group had twelve sessions of EMGBio once a week. At the end of the sessions, all athletes were revaluated. Results: At a velocity of 30 deg/s, the ankle eversion peak torque of 0.18 seconds (PT of 0.18s) was higher in the training group and at a velocity of 60 deg/s, the knee flexion PT of 0.18s was higher in the training group. Conclusion: Electromyographic biofeedback improved the isokinetic parameters of the amateur soccer players.